1997
DOI: 10.1084/jem.186.5.705
|View full text |Cite
|
Sign up to set email alerts
|

Altered Proliferative Response by T Lymphocytes of Ly-6A (Sca-1) Null Mice

Abstract: Ly-6A is a murine antigen which is implicated in lymphocyte activation and may be involved in activation of hematopoietic stem cells. Antibody cross-linking studies and antisense experiments have suggested that Ly-6A is a lymphocyte coactivation molecule. To better understand the function of Ly-6A, we used gene targeting to produce Ly-6A null mice which are healthy and have normal numbers and percentages of hematopoietic lineages. However, T lymphocytes from Ly-6A–deficient animals proliferate at a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
109
2
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(124 citation statements)
references
References 67 publications
10
109
2
1
Order By: Relevance
“…These previously published observations indicate that expression of Ly-6A.2 is critical for activation through the Ag receptor. Contrary to the above studies, CD4 ϩ T cells from Ly-6A mutant mice are modestly hyper-responsive to anti-CD3 Ab compared with their wild-type littermates (37). In addition, T cells from Ly-6A.2-null mice have a prolonged proliferative response to Ag stimulation.…”
Section: Cd8contrasting
confidence: 46%
“…These previously published observations indicate that expression of Ly-6A.2 is critical for activation through the Ag receptor. Contrary to the above studies, CD4 ϩ T cells from Ly-6A mutant mice are modestly hyper-responsive to anti-CD3 Ab compared with their wild-type littermates (37). In addition, T cells from Ly-6A.2-null mice have a prolonged proliferative response to Ag stimulation.…”
Section: Cd8contrasting
confidence: 46%
“…32 Particularly interesting possibilities arise from the phenotype of mice lacking Ly-6A, T cells of which exhibit prolonged proliferative responses to antigen stimulation. 33 This suggests a down-regulatory function of Ly-6A. If a similar role for Ly-6G is hypothesized then it is tempting to imagine that antibody ligation of Ly-6G might remove an important negative regulator of neutrophil function, resulting in activation and the responses we have described.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of Ly-6A/E knockout mice (24) and disruption of the Ly-6C gene in NOD mice have revealed no function for these molecules in hemopoiesis. One explanation for these results is that some of the Ly-6SF members are functionally redundant, so that the loss of one gene is not sufficient to affect lymphoid cell development.…”
Section: Discussionmentioning
confidence: 99%
“…Gene knockouts have only been analyzed for Ly-6A/E, which suggested that the Ag may have an inhibitory role in regulating cell activation (24). Other studies have suggested roles in cell adhesion in lymphocytes (25) and bone marrow stroma (26) and in T cell Ag-specific immune responses (27).…”
mentioning
confidence: 99%